Repair of Anterior Palatal Fistula by Local Mucoperiosteal Flap - Ibrahim, Farzana Bilquis; Khundkar, Shafquat Hussain; Mannan, Iftekhar Ibne; Ahmed, Tanveer (Bangladesh Critical Care Journal, 2017)
Background: The closure of a residual post-palatoplasty anterior palatal fistula can be among the most difficult of all surgical techniques and remains challenging. No single technique is satisfactory and attempts at closure of these fistulae have been associated with high failure rate. The local mucoperiosteal flaps are a useful technique for closing such defect. This flap was selected for its alikeness and its abundant blood supply from the greater palatine vessels. It is also easily accessible, versatile and can be transposed without tension. Objective: To see the outcome of closure of anterior palatal fistula by local mucoperiosteal flap, and also to evaluate the efficacy of closure of this flap without complications such as recurrence. Methods: This is a prospective, non randomized, non controlled clinical trial that was carried out on 15 patients with anterior palatal fistula (Type V), who presented between the time of January 2010 to August 2011 in Medi-Aid hospital, Dhaka. Results: The clinical study comprised of 15 patients (n=15) with anterior palatal fistula with an average of 5.74 years of age. The average size of the fistula in the study group was seen to be 5.93 mm.Donor site morbidity such as haematoma, infection, vascular compromise, flap necrosis, flap dehiscence etc was low and hospital stay was shorter in comparison to a complicated palatal surgery. Conclusion: The clinical results indicated that anterior palatal fistula closure with local mucoperiosteal flap technique is relatively safe, uncomplicated and effective than the other bulky techniques that have been used across the world till date. Bangladesh Crit Care J March 2017; 5(1): 17-22